Pelatihan dan Pendampingan Penyusunan Asesmen Formatif Kurikulum Merdeka Mata Pelajaran Sejarah MGMP Sejarah Kabupaten Kudus - Suwito Eko Pramono; Syaiful Amin; Nanda Julian Utama; Junaidi Fery Lusianto; Nathanael Agung Kristanto; Siti Khusnul Khotimal; Dhoni Firzky Arya Sahab (Universitas Teuku Umar, 2024)
As an effort to improve and catch up on learning loss as a result of the Covid-19 pandemic, the government has implemented an independent learning curriculum in most educational institutions at various levels. However, as a result of the lack of preparation for the implementation of this curriculum, various problems arose, especially in terms of formative assessment. Problems regarding formative assessment in the implementation of the independent learning curriculum were also experienced by the Kudus Regency History MGMP. The aim of this activity is an effort to reduce partner problems through collaborative activities in the form of community service. The method in this activity is training, followed by post-training assistance. The results of the service activities show that there is an increase in partners' understanding of the preparation of formative assessments for history learning. This is evidenced by the evaluation results in each activity carried out. During the training and mentoring activities, participants were also very enthusiastic and held discussions with resource persons. Thus, it can be said that this activity has a positive impact and changes to partners, especially in terms of preparing formative assessments for learning history.